Modulation of esophageal afferent pathways by 5‐HT3 receptor inhibition. Issue 5 (29th January 2013) - Szczesniak, M. M.; Fuentealba, S. E.; Zhang, T.; Cook, I. J.
Abstract Background The study aims were to investigate whether neural pathways involving 5‐HT3 receptors mediate: (i) distension‐induced upper esophageal sphincter (UES) relaxation reflex, (ii) esophageal sensitivity to acid and electrical stimuli, and (iii) viserosomatic sensitization following acid exposure. Methods In Study I, in a double‐blind crossover trial (n = 9) esophageal sensory and pain thresholds to electrical stimulation were measured in the esophagus, midsternum, and the foot, before subjects were randomized to receive either Ondansetron (8 mg i.v.) or NaCl (0.9% w/v). HCl (0.15 mol L−1) was then infused into distal esophagus and electrical thresholds were reassessed. Following electrical sensory threshold testing, subjects received a second esophageal infusion of HCl to evaluate esophageal sensitivity to acid. In Study II (N = 10), frequencies of distension‐induced UES relaxation responses were scored before and after treatment with Ondansetron and NaCl in a double‐blind crossover trial. Key Results In Study I, ondansetron had no effect on esophageal sensitivity to HCl or acid‐induced sensitization. However, blockade of 5‐HT3 receptors did reduce midsternum somatic pain thresholds. Sixty minutes after esophageal acid exposure, pain thresholds were significantly lower in the ondansetron arm (mean Δ−1.36 ± 0.4 mA) when compared with NaCl (mean Δ−0.14 ± 0.58 mA) (P < 0.05). In Study II, 5‐HT3 receptor blockade had no significant effect on UES relaxation reflex. Conclusions & Inferences This study does not support the hypothesis that in health, 5‐HT3 receptors play a significant role in esophago‐UES distention‐induced relaxation reflex and esophageal sensitivity to acid or electrical stimulation. It does provide new evidence for involvement of 5‐HT3 receptors in viscerosomatic sensitization.